Determinants of smallholders farmers participation in banana markets in central Africa: the role of transaction costs - Ouma, Emily A.; Jagwe, J.; Obare, G.A.; Abele, S. (Wiley, 2010)
A bivariate probit model was employed to jointly and separately estimate banana market participation decisions of buying and selling households in Rwanda and Burundi using household survey data. Selectivity bias was corrected for in estimating the transacted volumes using Heckman’s procedure. The results showed that transaction cost related factors such as geographical location of households, market information sources, and travel time to the nearest urban centre influence market participation. Non price related factors such as security of land tenure, labor availability, off farm income, gender of the household head and years of farming experience had a significant influence on the transacted volumes. Output prices had a significant effect on sales volume, providing incentives for increased supply by sellers. Generally, the findings suggest that policies aimed at investments in rural road infrastructure, collective marketing and value addition of banana products may provide a potential avenue for mitigating transactions costs and enhancing market participation and production of marketed surplus by rural households.